2022
DOI: 10.1002/anie.202209658
|View full text |Cite
|
Sign up to set email alerts
|

On the Bonding Nature in the Crystalline Tri‐Thorium Cluster: Core‐Shell Syngenetic σ‐Aromaticity

Abstract: A unique thorium-thorium bond was observed in the crystalline tri-thorium cluster [{Th(η 8 -C 8 H 8 )(μ 3 -Cl) 2 } 3 {K(THF) 2 } 2 ] ∞ , though the claim of σ-aromaticity for Th 3 bond has been questioned. Herein, a new type of core-shell syngenetic bonding model is proposed to describe the stability of this tri-thorium cluster. The model involves a 3c-2e bond in the Th 3 core and a multicentered (ThCl 2 ) 3 charge-shift bond with 12 electrons scattering along the outer shell. To differentiate the strengths of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 62 publications
(1 reference statement)
1
15
0
Order By: Relevance
“…30 Remarkably, a unique σ-aromatic thorium−thorium bond was recently observed in the crystalline tri-thorium cluster, 31 and the claim of such σ-aromaticity has been authenticated by the ab initio valence bond (VB) method. 32 Besides, metal clusters [Th@Bi 12 ] 4− and U 4 (NH) 4 have also been found to exhibit single and double aromaticity, respectively. 33,34 It is worthy to note that Kiplinger and co-workers prepared metallabiphenylenes containing an aromatic benzene ring and an antiaromatic cyclobutadiene ring.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Remarkably, a unique σ-aromatic thorium−thorium bond was recently observed in the crystalline tri-thorium cluster, 31 and the claim of such σ-aromaticity has been authenticated by the ab initio valence bond (VB) method. 32 Besides, metal clusters [Th@Bi 12 ] 4− and U 4 (NH) 4 have also been found to exhibit single and double aromaticity, respectively. 33,34 It is worthy to note that Kiplinger and co-workers prepared metallabiphenylenes containing an aromatic benzene ring and an antiaromatic cyclobutadiene ring.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since the 5 f atomic orbitals (AOs) are rather contracted and 6 d AOs are energetically high, the bonding involving actinides is predicted to be weak and localized. In other words, actinides are rarely found to participate in strong and delocalized aromaticity, typically with a light 2 p element . Remarkably, a unique σ-aromatic thorium–thorium bond was recently observed in the crystalline tri-thorium cluster, and the claim of such σ-aromaticity has been authenticated by the ab initio valence bond (VB) method . Besides, metal clusters [Th@Bi 12 ] 4– and U 4 (NH) 4 have also been found to exhibit single and double aromaticity, respectively. , It is worthy to note that Kiplinger and co-workers prepared actinide 2-metallabiphenylenes containing an aromatic benzene ring and an antiaromatic cyclobutadiene ring …”
Section: Introductionmentioning
confidence: 99%
“…[7] Very recently, Lin and Mo provided further computational data supporting the chargeshift bonding in the actinide cluster, and found that the overall charge transfer between thorium and chlorine atoms is about ten times more stabilizing than electron delocalization in the Th3 ring. [8] The authors linked the latter with the stabilization effect resulting from the periodic boundary conditions (PBC) for the electron distribution, [9] and made the conclusion that the trithorium bonding is therefore "truly delocalized and σ-aromatic". [8] Similar conclusions were drawn by Tomeček et al [10] who utilized the entire arsenal of sophisticated computational methods to demonstrate that the Th3 ring contains cyclically delocalized electrons and should be regarded σ-aromatic.…”
Section: Introductionmentioning
confidence: 99%
“…[8] The authors linked the latter with the stabilization effect resulting from the periodic boundary conditions (PBC) for the electron distribution, [9] and made the conclusion that the trithorium bonding is therefore "truly delocalized and σ-aromatic". [8] Similar conclusions were drawn by Tomeček et al [10] who utilized the entire arsenal of sophisticated computational methods to demonstrate that the Th3 ring contains cyclically delocalized electrons and should be regarded σ-aromatic. However, in both works the simplified highly ionized model cluster Th3Cl6 4+ https://doi.org/10.26434/chemrxiv-2022-hn1vh-v4 ORCID: https://orcid.org/0000-0002-2013-0617 Content not peer-reviewed by ChemRxiv.…”
Section: Introductionmentioning
confidence: 99%
“…The design of polymetallic assemblies is attracting high interest in uranium chemistry because of their ability to promote small molecule activation, [1][2][3][4][5][6][7][8][9][10] and their interesting magnetic properties, [11][12][13][14][15] yet synthetic routes to such assemblies remain elusive. Moreover, the recent identification of the first example of actinide metal-metal bonding interactions in a trinuclear thorium complex 16,17 suggests that trinuclear assemblies may be used to promote metal-metal interactions in uranium compounds. Nevertheless, examples of trinuclear uranium complexes [18][19][20][21][22][23][24][25] remain rare with only two examples reported so far for the +III oxidation state.…”
mentioning
confidence: 99%